Crystal structure and Hirshfeld surface analysis of 1,3,3,4,4,5,5-heptafluoro-2-(3-[(2,3,3,4,4,5,5-heptafluorocyclopenten-1-yl)oxy]-2-{[(2,3,3,4,4,5,5-heptafluorocyclopenten-1-yl)oxy]methyl}-2-methylpropoxy)cyclopentene - Andrew J. Peloquin; Gary J. Balaich; Abby R. Jennings (Acta Crystallographica Section E: Crystallographic Communications)
In the title compound, C20H9F21O3, a central sp3-hybridized carbon atom is decorated with three heptafluoro-2-methyloxy(cyclopent-1-ene) arms and a methyl group. The primary packing is determined by C—F...F—C interactions, forming [001] chains, which are consolidated via weaker C—F...F—C and C—H...F—C contacts. A Hirshfeld surface analysis was conducted to aid in the visualization of these various influences on the packing: this revealed that the largest contribution to the surface contacts arises from F...F interactions (53.5%), followed by F...H/H...F (34.5%) and F...C/C...F (7.1%).